First report of a carbapenemase gene blaOXA-181 harbored in a conjugative plasmid in Kluyvera sichuanensis isolated from spinach - Xu Yang; Jinkyung Kim; Nhu-Y Do; Xinhui Li; En Huang; Se-Ran Jun; Sun Hee Moon; Erin L. DiCaprio; Shuting Chen (International Journal of Food Microbiology, 2026)

Genetic diversity and distribution pattern of three economically important species of Bangiaceae (Rhodophyta) along China's coast revealed by rbcL - Meng-Xue Xu; Jia-Qiu Pu; Wei Zhou; Cui-Cui Tian; Guang-Ping Xu; Li-En Yang (Estuarine, Coastal and Shelf Science, 2026)

Experimental and numerical investigation of thermal hydraulic performance of the shell and tube steam superheater - Wentao Hao; De-en Song; Wenwen Zhang; Zhenlei Liu; Weihua Li; Xingtuan Yang (Annals of Nuclear Energy, 2026)

Feasibility of producing specific pathogen-free gibel carp (Carassius auratus gibelio var. CAS III) by selective breeding of Myxobolus honghuensis-free broodstock - En Bang Shao; Fan Zhou; Li Qiang Zhang; Jian Chun Shao; Yang Liu (Aquaculture, 2026)

Comprehensive analyses of carbapenem-resistant and ESBL-producing bacteria in fresh vegetables and their resistome in the United States - Sun Hee Moon; Xu Yang; Jinkyung Kim; Elizabeth Leighton; Se-Ran Jun; Erin DiCaprio; Chelsea Gale; Shuting Chen; Xinhui Li; En Huang (Food Research International, 2026)

Acquisitive, diverse tree stands resist vine invasion via contrasting temporal effects on crown volume and herb cover - Li Zhang; Liting Zheng; Marc W. Cadotte; Charles A. Nock; Baiyu Yang; Zhiming Hu; Ciliang Zhao; Wen-Hui You; En-Rong Yan (Forest Ecology and Management, 2026)

A promising strategy to battle Enterocytozoon hepatopenaei infection in shrimp: dual action of paeonol on spore inhibition and immune activation - Li-Peng Shan; Mao-Mao Wang; Si-En Wang; Yang Hu; Lei Liu; Jiong Chen (Aquaculture, 2026)

Efficient capture of Cs+ ions by two supertetrahedral cluster-based microporous metal chalcogenides in neutral and alkaline environments - Ya-Dong Wu; Lu Yang; Zhi-Hua Chen; Hai-Yan Sun; Chuan Lv; Xiao-Ying Huang; En-Chao Li; Mei-Ling Feng (Journal of Hazardous Materials, 2026)

Identification, characterization, and mechanism of action of subtilisin-like Sy-1 from Bacillus amyloliquefaciens X-YJ-1 against Listeria monocytogenes - Zhen Zhang; Bingbing Xiong; Jinping Yan; Chenjian Liu; Xiaoran Li; En Yang (Food Bioscience, 2026)

Influence of curing temperature on the carbonation products and mechanical performance of reactivated cementitious materials - Ye Li; Yutong Ju; En-hua Yang; Bing Zhang; Tiejun Liu (Waste Management, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

Fourier transform ion cyclotron resonance mass spectrometry revealed molecular diversity and complexity of dissolved organic matter in the influent and effluent of 49 wastewater treatment plants - Xuexin Gong; En Hu; Zhineng Hao; Fang Yang; Baozhu Pan; Ming Li (Journal of Environmental Chemical Engineering, 2026)

Reduced-order modeling of particle-fluid flows with heat transfer via a curriculum learning approach - Michael Castro; Shuo Li; Kai-en Yang; Toshiki Imatani; Mikio Sakai (Chemical Engineering Journal, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Decumbic acid derivatives from soil fungus Lasiodiplodia sp. BG1083 - Hong-Qiao Dai; Xiao-Bing Su; En-Tao Zhou; Wen-Ting Li; Shuang-Shuang Chen; Hui-Yang Cao; Lin Hu; Meng-Yuan Jiang (Natural Product Research, 2026)

Quantitative scattering analysis of rough surface based on the boundary scattering matrix - Yang-pu Chen; Li-Yun Fu; Qing-qing Li; Hong-en Li; Qing-he Meng (Applied Geophysics, 2026)

Novel biodiversity and biogeography insights of filamentous Bangiales (Rhodophyta) from China - Yan-De Wang; Yin-Yin Deng; Cui-Cui Tian; Han-Ru Ge; Wei Zhou; Nan-Jing Ji; Li-En Yang (Algae, 2026)
The taxonomy of filamentous Bangiales was challenging due to its plastic and simple morphology. Molecular approaches play a significant role in revealing cryptic biodiversity and resolving phylogenetic relationships. Nonetheless, the biodiversity of filamentous Bangiales in many regions, including China, has not been thoroughly investigated yet using updated methods. In this study, we investigated the biodiversity of filamentous Bangiales in China, employing a more comprehensive and detailed sampling approach. The rbcL and 18S gene sequences (partial or complete) of 49 specimens collected from 37 sites were obtained. Phylogenetic analysis resolved these specimens into four clades, including Bangia, ‘Bangia’ 1, ‘Bangia’ 2, and Pseudoganglia. Seven putative species were delineated using empirical methods, including Automatic Barcode Gap Discovery (ABGD), General Mixed Yule Coalescent (GMYC), and Bayesian Poisson tree processes (bPTP), as well as genealogical analysis. Among them, four were species previously reported, two were cryptic species, and the other was a new record in China. The distribution of these molecularly delineated species was mapped along China’s coastline. Similar to the bladed Bangiales, antitropical, transoceanic, and thermal-gradient distribution patterns were also observed for filamentous Bangiales on a global scale. The ancestral region was retraced by incorporating species data from China into existing datasets using BioGeoBEARS with BAYAREALIKE + J as the best-supported model. Under this model, East Asia shows the highest marginal probability as the ancestral area for the crown clade, though uncertainty remains across alternative regions. A most parsimonious expansion scenario of Bangiales from east Gondwana to other regions of the world was proposed.

Nanobubble aeration accelerates manure wastewater sanitisation and enhances nitrogen retention while reduces greenhouse gas emissions - Shance Hou; En Xie; Buchun Si; Yang Xiao; Jingtao Ding; Zhuoyu Yan; Haibin Zhou; Hongsheng Cheng; Yujun Shen; Yunkai Li (Water Research, 2026)

Allelopathic metabolite accumulation and microbial dysbiosis underlying continuous cropping disorder in the Panax ginseng rhizosphere - Yang-Bin Lai; Jia-Qi Wang; Li-Ye Cheng; Yuan Zhao; Jin-Qi Wang; Jin-Hea Jeoun; Qi Yan; Chang-Bao Chen; En-Peng Wang (Physiological and Molecular Plant Pathology, 2026)

Regulation of ferroptosis with natural compounds: potential applications in the treatment of acquired brain injury - Haonan Zhu; Peidi Li; Zherui Xing; Bo Yang; Fei Zheng; Zhe Yu; Wei Zhang; Xueping Yang; Jiekun Luo; Tao Tang; Yang Wang; En Hu; et al. (Phytochemistry Reviews, 2026)

Transcriptomic atlas demonstrates the diurnal partitioning of physiological activities of the intertidal red algal seaweed Neoporphyra haitanensis - Dexin Lyu; Jia Liu; Libao Zheng; Zihan Ge; Chuanming Hu; Li-En Yang; Shan Lu; Kui Li; Yinyin Deng (Aquaculture, 2026)

Synergetic activation of both peroxydisulfate and bisulfite by Fe³⁺ for efficient singlet oxygen generation and organic pollutant degradation - Xin Zhang; Kangning Huangfu; Xiafei Meng; Jinghua Li; Junpei Ye; Yingxuan Deng; Zhihua Chen; Dapeng Wu; Kai Jiang; Guang-En Yuan; Fenglin Yang (Process Safety and Environmental Protection, 2026)

Biomimetic enzyme electrochemical sensor based on nanocomposites of carbon black coated ZnO nanoflowers/poly (L-phenylalanine) for food colorant analysis - En Han; Ming Bao; Yang Li; Xiaoya Dong; Jianrong Cai (Food Bioscience, 2026)

Purification and characterization of an exopolysaccharide produced by Lactiplantibacillus plantarum YM-4-3 strain isolated from home-made Yunnan Tempeh - Bingbing Xiong; Yonggang Xiong; Tianzhao Si; Xiaoran Li; Chenjian Liu; Jinping Yan; En Yang (Archives of Microbiology, 2026)

Dual-enhanced multifunctional molecularly imprinted electrochemical sensor with specificity and signal amplification for tartrazine analysis - En Han; Ming Bao; Yang Li; Jianrong Cai (Food Chemistry, 2025)

TAX1BP1 regulates the apoptosis of renal tubular epithelial cells in ischemia/reperfusion injury via the NF-kB/PMAIP1 signaling pathway - Zhifen Wu; Wei Tan; Chunxuan Wang; Lirong Lin; En Tian; Bengang Huo; Luquan Zheng; Xujia Yang; Ke Li; Jurong Yang (Inflammation Research, 2025)

Progress in the application of DIC technology to rock mechanics testing: a review - Hao-fan Luo; Yang Tang; Wen-tao Feng; Jian-feng Liu; Hua Li; En-ze Zhou (Bulletin of Engineering Geology and the Environment, 2025)

Towards probabilistic interpretations for the deterministic magnetic inversion: A case study of borate deposits of Liaoning province, Northeast China - Ce Yang; Changwei Qi; Bing Liu; Xiujing Tang; Guitao Sun; Xiaolong Wei; Yingqiang Yu; Baochun Li; Gaofeng Ye; Ji’en Dong (Applied Geophysics, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

Regulating charge separation by structure adjusting in pyrene-based 1D COFs for efficient photocatalytic hydrogen evolution - Bing Han; Shuyan Wang; Xianglin Yu; Xuxin Fan; En Liang; Yao Yang; Huan Zhang; Changyu Qin; Junbo Li (Chemical Engineering Journal, 2025)

Responses of anuran diversity and community structure to an urbanization gradient in a subtropical Asian city - Yung-Chih Lai; Cheng-En Li; Wei-Chun Cheng; Tien-Chen Lai; Pei-Fen Lee; Yi-Ju Yang (Urban Ecosystems, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Regulation of coupled carbon‑sulfur interactions by Spartina alterniflora via physicochemical properties and microorganism-mediated pathways in coastal wetlands - Yu-Xiang Zhu; Pei-Feng Li; Chun-Ying Liu; Jiang-Chen Gong; En-Ren Zhang; Jing-Wen Hu; Qian-Qian Yang; Gui-Peng Yang (Chemical Geology, 2025)

Deciphering the miRNA–mRNA Interaction Network Regulating Aging Skeletal Muscle in Various Exercise Regimens through Comprehensive Bioinformatics Analysis - Zhi Yu; Pin-Shi Ni; Zhuang-Zhi Wang; Zheng-Yang Zhao; Bao-Yi Chen; Zhen-En Zhang; Fang-Hui Li (Cell Biochemistry and Biophysics, 2025)

Biofouling control strategy through denatured extracellular proteins: An empirical evidence from reclaimed water distribution systems - Yan Shen; Yang Xiao; En Xie; Jaume Puig-Bargués; Yuqian Yao; Naikun Kuang; Yunkai Li (Water Research, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

Bacteria in the Phylum Bacillota Degrade Nicotine Through the Variant of Pyridine and Pyrrolidine Pathway - Xiu-Ming Liu; Xuan Hai; Cong-Jian Li; Yu-Fan Han; Xing Chen; Yu-Jin Fan; Jian Wu; En-Min Zhou; Yuan-Dong Li; Ling-Ling Yang; Yan-Qing Duan; Xiao-Yang Zhi (Current Microbiology, 2025)

The mouse resource at National Resource Center for Mutant Mice of China - Bingzhou Han; Dongshen Chen; Zhong Chen; Ting Wang; Kaiyuan Zi; Rui Feng; Xiaoliu Yang; Ling’en Li; Juan Liang; Xiang Gao (Mammalian Genome, 2025)

Associations between in utero exposure of per- and polyfluoroalkyl substances (PFAS) mixture and anthropometry measures at birth - Nan Zhao; Xiaozhen Zhang; Yahui Li; Haoyu Zhang; En Yang; Lei Ding; Yi Liu (Environmental Pollution, 2025)

Soil viruses regulate soil nutrient cycling through themselves and their effects on host functioning to impede the growth of continuously planted Casuarina equisetifolia - Yu-Hua Wang; Lei Hong; Yi Lin; Miao-En Qiu; Jian-Juan Li; Qing-Xu Zhang; Xiao-Li Jia; Yu-Lin Wang; Li-Yuan Wang; Yang-Xin Luo; Wen-Xiong Lin; Hai-Bin Wang; et al. (Applied Soil Ecology, 2025)

Mitigating quinolones contamination using Cyanophyta, Chlorophyta, and Bacillariophyta: Removal efficiency, degradation pathways and products - Yang Liu; Jiaxin Sui; Xinrui Fan; Tianli Zhang; Manogaran Lakshmikandan; Changshun Sun; En Hu; Ming Li (Journal of Water Process Engineering, 2025)

A Gln alteration influences leaf morphogenesis by mediating gibberellin levels in tobacco - Qi-Li Mi; Hong-Tao Lv; Fei-Fei Huang; Li Xu; Zi-Ying Huang; Wen-Wu Yang; Mei-Yun Zou; Hai-Tao Huang; Wan-Li Zeng; Jia-Yin Zhao; Qing-Xian Chen; Yong-En Si-Tu; et al. (Journal of Plant Physiology, 2025)

Herbaceous competition does not affect positive tree diversity effects on seedling crown complementarity - Muhammad Abdullah; Li-Ting Zheng; Li Zhang; Bai-Yu Yang; Xiao-Chen Fang; Di-Feng Bao; Samreen Ghulam Rasool; Ci-Liang Zhao; En-Rong Yan (Forest Ecology and Management, 2025)

Correction to: Autophagy in Oligodendrocyte Lineage Cells Controls Oligodendrocyte Numbers and Myelin Integrity in an Age-dependent Manner - Hong Chen; Gang Yang; De-En Xu; Yu-tong Du; Chao Zhu; Hua Hu; Li Luo; Lei Feng; Wenhui Huang; Yan-Yun Sun; Quan-Hong Ma (Neuroscience Bulletin, 2025)

Autophagy in Oligodendrocyte Lineage Cells Controls Oligodendrocyte Numbers and Myelin Integrity in an Age-dependent Manner - Hong Chen; Gang Yang; De-En Xu; Yu-tong Du; Chao Zhu; Hua Hu; Li Luo; Lei Feng; Wenhui Huang; Yan-Yun Sun; Quan-Hong Ma (Neuroscience Bulletin, 2025)

Opposing island biogeographic effects of turnover and nestedness on beta-diversity of soil faunal communities between woodland and deforested grassland - Zengyan Li; Zengke Zhang; Anna Yang; Sufeng Pan; Junyong Zheng; Ling Mou; Wensheng Chen; Tian Zhang; Liyi Zhou; Wenhui You; David A. Wardle; En-Rong Yan (Applied Soil Ecology, 2025)

Construction of activated carbon/activated carbon fibre capacitive deionization composite electrode and its potential application in desalination of brackish water - Tongtong Huang; Xiaomei Dong; Weixiong Huang; Jianfeng Song; Qingsong Zheng; Zhaoyang Li; Yu Han; En Xie; Shimin Wang; Yuhui Yang; Zhanming Tan (Desalination, 2025)

The obesity-related mutation gene on nonalcoholic fatty liver disease - Yen-Yu Chen; Chi-Sheng Chen; Jee-Fu Huang; Wen-Hsiu Su; Chia-Yang Li; Wei-Shiun Chen; En-Sheng Lin; Wan-Long Chuang; Ming-Lung Yu; Shu-Chi Wang (Human Genetics, 2025)

Diurnal rhythm of carotenoid metabolism in the intertidal red algal seaweed Neoporphyra haitanensis - Dexin Lyu; Zihan Wang; Li-En Yang; Chuanming Hu; Shan Lu; Yinyin Deng (Algal Research, 2025)

Tissue distribution and residue depletion of difloxacin in crucian carp (Carassius carassius) after multiple oral administration - Fan Yang; Kai-Li Ma; Yue Liu; Yang-Guang Jin; Yan-Ni Zhang; Yan Dai; Ming-Hui Duan; Ze-En Li; Fang Yang (Aquaculture, 2024)

Bisulfite enhances p-nitrophenol degradation by zero-valent iron under oxic conditions: Combination of indirect reduction by superoxide radical and direct reduction - Guang-En Yuan; Yan-Ge Ma; Kangning Huangfu; Yunbei Li; Xin Zhang; Fenglin Yang (Journal of Environmental Chemical Engineering, 2024)

Hydro-morphology and water quality jointly shape the structure and network stability of the plankton community in multi-tributary river basins - Chao Chang; En Hu; Xudong Xue; Juan Li; Dou Du; Fang Yang; Ming Li (Journal of Hydrology, 2024)

Fault structures of the Haichenghe fault zone in Liaoning, China from high-precision location based on dense array observation - Qing-Shan Sun; Lan-Shu Bai; Liang Wang; Jiu-Yang Wang; Shi-Chao Yang; En-Lai Li (Journal of Seismology, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Output Feedback Adaptive Optimal Control of Multiple Unmanned Marine Vehicles with Unknown External Disturbance - Liang-En Yuan; Yang Xiao; Tieshan Li; Dalin Zhou (Journal of Marine Science and Engineering, 2024)
This paper presents an optimal output-feedback tracking control problem for multiple unmanned marine vehicles (UMVs) to track a desired trajectory. To guarantee the control objective in an optimal manner, adaptive dynamic programming (ADP) with optimal compensation terms is adopted. A neural velocity observer is designed based on a neural network (NN) to estimate the unmeasured system states and the unknown system dynamics. Furthermore, a disturbance observer (DO) is proposed to go against the effect of the unknown external disturbance of the sea environment. It is proved that the proposed controller can guarantee that all signals in the closed-loop system are bounded. Simulation results are given to demonstrate the effectiveness of the proposed control algorithm.

A novel scheme for shore power data to enhance containership-at-berth emission estimation - Jinggai Wang; Huanhuan Li; Zaili Yang; Ying-En Ge (Transportation Research Part D: Transport and Environment, 2024)

A pooled mycoviral resource in a strain of Rhizoctonia solani are regulators of fungal virulence - Ya Rong Wang; Jia En Su; Zhi Juan Yang; Jie Zhong; Xiao Gang Li; Yi Chen; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2024)

MOF-derived CoP/C catalyst for efficient dibenzothiophene hydrodesulfurization - Liang-Liang Zhang; Kai-Xuan Yang; Cai-Long Xue; Wan-Xi Li; Bo-Qiong Li; Yi-En Du; Yong-Qiang Chen; Ya-Jie Liu (Fuel, 2024)

Versatile MOF-based nanofibrous heterostructures for engineering the CO2 photoreduction activity and selectivity: From CO to C2H5OH - Xu-Chao Xia; Feng Cheng; Peng Sun; Amare Aregahegn Dubale; Hao Han; En-Tian Cui; Jun Song; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2024)

A Multidrug-Resistant Extended-Spectrum Beta-Lactamase (ESBL)-Producing Enterobacter hormaechei Strain from Mixed Sprouts - Elizabeth A. Leighton; Chelsea N. Gale; En Huang; Xu Yang; Erin L. DiCaprio; Xinhui Li (Current Microbiology, 2024)

Mixing states and secondary formation processes of organic nitrogen-containing single particles in Guangzhou, China - Lijun Yun; Chunlei Cheng; Suxia Yang; Zaihua Wang; Mei Li; Qi En Zhong; Liyuan Mao; Sulin Liu; Xiaoya Cheng; Duanying Chen; Fan Yang; Zhen Zhou (Journal of Environmental Sciences, 2024)

Environmental exposure to per- and polyfluoroalkyl substances mixture and asthma in adolescents - Yi-Fan Wang; Li Li; Xu Wang; Ya-Nan Yun; Xue-Lin Wang; En-Yang He; Ming-Kun Song; Xue-Hong Xia; Ying-Xue Zou (International Archives of Occupational and Environmental Health, 2024)

Genome-wide identification and quantification of salinity-responsive Na+/K+-ATPase α-subunits in three salmonids - Yue Su; Shuang-En Yu; Yong-Xu Sun; Liang Zhang; Yue Tan; Yu-Yang Zhang; Shuo Wang; Yan-Gen Zhou; Li-Sha Hu; Yun-Wei Dong (Aquaculture, 2024)

IiAGL6 participates in the regulation of stamen development and pollen formation in Isatis indigotica - Liu Yang; Xin Qiao; Hao-En He; Wei-Wei Yi; Ya-Nan Gao; Xiao-Min Tan; Hao Cheng; Xiao-Fang Hou; Ye-Ye Ma; Hong-Li Wang; Xuan Huang; Yan-Qin Ma; et al. (Plant Science, 2024)

Niche processes shape zooplankton community structure in a sediment-laden river basin - Zijie Yang; Baozhu Pan; Xinyuan Liu; En Hu; Gang Li; Jingxiang Hu; Zhenyu Huang (Hydrobiologia, 2024)

Exploring intrinsic distribution of phytoplankton relative abundance and biomass in combination with continental-scale field investigation and microcosm experiment - Sisi Ye; Ling Wen; Li Gao; Junyi Zhang; Haihan Zhang; Songqi Yang; En Hu; Jianming Deng; Man Xiao; Arash Zamyadi; Baozhu Pan; Ming Li (Water Research, 2024)

The Trail-Following Communication in Stylotermes faveolus and S. halumicus (Blattodea, Isoptera, Stylotermitidae) - Himanshu Thakur; Surbhi Agarwal; Jaromír Hradecký; Garima Sharma; Hou-Feng Li; Shang-En Yang; Hana Sehadová; Ravinder S. Chandel; Mirek Hyliš; Vartika Mathur; Jan Šobotník; David Sillam-Dussès (Journal of Chemical Ecology, 2023)

Speciation and gas-liquid equilibrium study of CO2 absorption in aqueous MEA-DEEA blends - Rui Zhang; Haonan Liu; Ruixi Liu; Yingjie Niu; Luning Yang; Francesco Barzagli; Chao'en Li; Min Xiao (Gas Science and Engineering, 2023)

The long-term effects of thinning on soil respiration vary with season in subalpine spruce plantations - Long-Fei Chen; Zhi-Bin He; Wen-Zhi Zhao; Lei Ma; Sheng-En Liu; Li-Wen Zhao; Shu-Ping Yang; Xiang-Yan Feng (Agricultural and Forest Meteorology, 2023)

MD-YOLO: Multi-scale Dense YOLO for small target pest detection - Yunong Tian; Shihui Wang; En Li; Guodong Yang; Zize Liang; Min Tan (Computers and Electronics in Agriculture, 2023)

Occurrence, distribution and risk assessment of phthalate esters in 51 urban wastewater treatment plants in Shaanxi Province, China - Xiaoyu Wang; En Hu; Chenghua Yang; Ming Li (Journal of Environmental Chemical Engineering, 2023)

Managing plant density and nitrogen fertilizer to reduce nitrogen input without yield reduction of late-sown cotton after wheat by improving light interception and sink nitrogen partitioning in a double cropping system - Zhao Zhang; Shoaib Ahmed; Muhammad Sohaib Chattha; Anda Liu; Jiahao Liu; Na Lv; Lirong Yang; Xuefeng Ma; Xian'en Li; Feiran Hao; Guozheng Yang (Field Crops Research, 2023)

Temperature sensitivity of marine macroalgae for aquaculture in China - Yu-Yang Zhang; Shuang-En Yu; Wen-Lei Wang; Li-En Yang; Qin-Qin Lu; Chao-Tian Xie; Tao Liu; Yun-Wei Dong (Aquaculture, 2023)

Deployment optimization of battery swapping stations accounting for taxis’ dynamic energy demand - Tian-yu Zhang; En-jian Yao; Yang Yang; Long Pan; Cui-ping Li; Bin Li; Feng Zhao (Transportation Research Part D: Transport and Environment, 2023)

ARHGEF15 is expressed in undifferentiated spermatogonia but is not required for spermatogenesis in mice - Yu-Jun Wang; Shuang Li; Hai-Ping Tao; Xiao-Na Zhang; You-Gui Fang; Qi-En Yang (Reproductive Biology, 2023)

Composition of dissolved organic matter (DOM) in wastewater treatment plants influent affects the efficiency of carbon and nitrogen removal - Ling Wen; Fang Yang; Xuan Li; Siwan Liu; Yuye Lin; En Hu; Li Gao; Ming Li (Science of The Total Environment, 2023)

Causal effects of air pollution on mental health among Adults——An exploration of susceptible populations and the role of physical activity based on a longitudinal nationwide cohort in China - Ke Ju; Liyong Lu; Wen Wang; Ting Chen; Chenyu Yang; En Zhang; Zongyou Xu; Shanshan Li; Jiangning Song; Jay Pan; Yuming Guo (Environmental Research, 2023)

The association between short-term ambient sulfur dioxide exposure and hospitalization costs of ischemic stroke: a hospital-based study in Chongqing, China - En-Jie Tang; Yu-Meng Zhou; Li-Li Yang; Nan Wang; Yue-Xu Jiang; Hua Xiao; Yue-Gu Hu; Da-Wei Li; Na Li; Qing-Song Huang; Ning Du; Ya-Fei Li; et al. (Environmental Science and Pollution Research, 2022)

Studying bona fide SARS-CoV-2 biology in a BSL-2 biosafety environment using a split-virus-genome system - Yingxin Ma; Guobin Mao; Weishan Yang; Guoqiang Wu; Guoqiang Li; Xiaoying Li; Xin Lin; Junnan Lu; Shijun Zhao; Wei Zhao; Junbiao Dai; Xian-En Zhang (Science China Life Sciences, 2022)

Optimal Design of the Seepage Control for Xianglushan Diversion Tunnel Under High External Water Pressure - Zhen-jie Zhang; Chun-pin Zeng; Hu Li; Yang Gao; Liang Gong; Yu-xing Li; Hai-fang Liang; En-zhong Zhang (Geotechnical and Geological Engineering, 2022)

The relationship between short-term PM2.5 exposure and outpatient visits for acne vulgaris in Chongqing, China: a time-series study - Xiang Li; Lai-Xin Zhou; Li-Li Yang; Xiao-Long Huang; Nan Wang; Yue-Gu Hu; En-Jie Tang; Hua Xiao; Yu-Meng Zhou; Ya-Fei Li; Yuan-Gang Lu; Tong-Jian Cai (Environmental Science and Pollution Research, 2022)

Aquapteridospora jiangxiensis, a new aquatic hyphomycetous fungus from a freshwater habitat in China - Su-Qin Peng; Yu-Lin Liu; Jun-En Huang; Xiao-Hong Li; Xin-Yi Yan; Hai-Yan Song; Yang Gao; Zhi-Jun Zhai; Yuan-Qiu Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Human telomerase reverse transcriptase (hTERT) synergistic with Sp1 upregulate Gli1 expression and increase gastric cancer invasion and metastasis - Lingyi Wu; Sumin Wang; Bo Tang; Li Tang; Yuanyuan Lei; Yaojiang Liu; Min Yang; Guodong Yang; Dan Zhang; En Liu (Journal of Molecular Histology, 2021)

Decreased Plasma Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) Levels are Linked with Disease Severity in Patients with Liver Cirrhosis - Lian-Ying Yang; Ji-Ping Hou; En-Kun Han; Gang Qiao; Li-Bin Liu; Xue-Bo Men (International Journal of Peptide Research and Therapeutics, 2021)

Haplotype networks of Phycocalidia tanegashimensis (Bangiales, Rhodophyta) indicate a probable invasion from the South China Sea to Brazil - Wan Zhao; Lei Dong; Dang Diem Hong; Juliet Brodie; Wei-Zhou Chen; Dam Duc Tien; Wei Zhou; Qin-Qin Lu; Mei-Ru Zhang; Li-En Yang (Marine Biodiversity, 2021)

Late Pennsylvanian carbonate platform facies and coral reef: new insights from southern China (Guizhou Province) - Marine Maillet; Wen-Tao Huang; Xiao Li; Zhen-Yuan Yang; Chang-Qing Guan; Yong-Li Zhang; En-Pu Gong; Katsumi Ueno; Elias Samankassou (Facies, 2021)
The Pennsylvanian is characterized by intense paleoenvironmental changes related to glacio-eustatic sea-level fluctuations and major tectonic events, which affected the evolution of biocommunities. Most known Pennsylvanian tropical reefs and mounds are predominantly composed of calcareous algae (e.g. phylloid algae, Archaeolithophyllum ), calcareous sponges, fenestrate bryozoans, Tubiphytes , and microbialites. However, in Houchang (southern China), the Late Pennsylvanian carbonate platform records a large coral reef lacking any analogs in age (Gzhelian), size (80–100 m thick) and composition (high biodiversity). The large coral reef developed at the border of the Luodian intraplatform basin. The intraplatform basin is characterized by the deposition of green algal grainstone, coated grain grainstone and bioclastic packstone, grainstone, floatstone and rudstone in shallow-waters. In the deep-water shelf, lithofacies are composed of burrowed bioclastic wackestone, microbioclastic peloidal packstone, grainstone, and fine-grained burrowed wackestone and packstone. In this context, the coral reef developed on a deep-shelf margin, in a moderate to low energy depositional environment, below the FWWB. The scarcity of Pennsylvanian coral reefs suggests global unfavorable conditions, which can be attributed to a complex pattern of several environmental factors, including seawater chemistry (aragonite seas), paleoclimatic cooling related to continental glaciation, and the biological competition with the more opportunistic and adaptive phylloid algal community that occupied similar platform margin paleoenvironments. The existence of the large Bianping coral reef in southern China, as well as a few additional examples of Pennsylvanian coralliferous bioconstructions, provides evidence that coral communities were able to endure the Late Paleozoic fluctuating paleoenvironmental conditions in specific settings. One of such settings appears to have been the deep shelf margin, where low light levels decreased competition with the phylloid algal community.

Magnesium decreases aluminum accumulation and plays a role in protecting maize from aluminum-induced oxidative stress - Xiangying Kong; Zhongping Peng; Dongxu Li; Wenna Ma; Ruidong An; Dawood Khan; Xinxun Wang; Yuan Liu; En Yang; Yuzhi He; Liqngquan Wu; Baige Zhang; et al. (Plant and Soil, 2020)

Brief report of the first cured 2019-nCoV pneumonia patient in West China Hospital - En-Qiang Chen; Li-Chun Wang; Guang-Min Tang; Yao Yang; Min-Jin Wang; Rong Deng; Fang Chen; Meng-Lan Wang; Ya-Chao Tao; Ping Feng; Hong Tang (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Functional Analysis of Sheep POU2F3 Isoforms - Guang-Wei Ma; Yan-Kai Chu; Hua Yang; Xiao-Hong Yan; En-Guang Rong; Hui Li; Ning Wang (Biochemical Genetics, 2020)
POU domain class 2 transcription factor 3 (POU2F3) plays an important role in keratinocyte proliferation and differentiation. Our previous study identified four sheep POU2F3 transcript variants ( POU2F3-1 , POU2F3-2 , POU2F3-3 , and POU2F3-4 ), encoding three POU2F3 protein isoforms (POU2F3-1, POU2F3-2, and POU2F3-3). However, the functional differences among the three POU2F3 isoforms remain unknown. The objective of this study was to determine the tissue expression pattern of the four POU2F3 transcript variants in sheep and to investigate the functional differences in cell proliferation among the three POU2F3 isoforms. Quantitative RT-PCR analysis showed that the four POU2F3 transcripts were ubiquitously expressed in all tested adult sheep tissues, and POU2F3-1 exhibited higher expression level than the other three POU2F3 transcript variants in skin ( P P P P > 0.05). Dual luciferase reporter assays demonstrated that overexpression of any one of the three POU2F3 isoforms significantly inhibited the promoter activities of keratin 14 ( KRT14 ) and matrix metalloproteinase 19 ( MMP19 ) genes ( P KRT14 and MMP19 genes than POU2F3-1 and POU2F3-2 ( P P > 0.05). These results suggest three sheep POU2F3 isoforms have similar functional effects, but to a different extent.

Multi-hole joint acquisition of a 3D-RVSP in a karst area: Case study in the Wulunshan Coal Field, China - Ming-Shun Hu; Dong-Ming Pan; Fu-Bao Zhou; Juan-Juan Li; Yang-Zhou Wang; Shen-En Chen; Yong-Zhong Xu (Applied Geophysics, 2020)

Effects of high-intensity interval training on adipose tissue lipolysis, inflammation, and metabolomics in aged rats - Lei Sun; Fang-Hui Li; Tao Li; Zhu Min; Luo-Dan Yang; Hao-En Gao; Da-Shuai Wu; Tian Xie (Pflügers Archiv - European Journal of Physiology, 2020)

Morphological characteristics and genetic diversity of Colletotrichum horii infecting persimmon tree in China - Quan-en Deng; Xiang-yang Ding; Jian-an Li; Lin-kai Cui; Jian-qiang Xu (European Journal of Plant Pathology, 2020)

Dysregulation of Fibroblast Growth Factor 10 in the Peripheral Blood of Patients with Schizophrenia - Yun Yu; Guo-Jun Xie; Yang Hu; Xue-Song Li; Guang-Yang Chen; Guang-En Zheng; Xi Chen; Yong Cheng (Journal of Molecular Neuroscience, 2019)

Serum Oxidative Stress Marker Levels in Unmedicated and Medicated Patients with Schizophrenia - Zhi-Le Bai; Xue-Song Li; Guang-Yang Chen; Yang Du; Ze-Xu Wei; Xi Chen; Guang-En Zheng; Wen Deng; Yong Cheng (Journal of Molecular Neuroscience, 2018)

Accurate Reconstruction of Porous Materials via Stochastic Fusion of Limited Bimodal Microstructural Data - Hechao Li; Pei-En Chen; Yang Jiao (Transport in Porous Media, 2018)

An inversion of transient electromagnetic data from a conical source - Hai-Yan Yang; Feng-Ping Li; Shen-En Chen; Jian-Hua Yue; Fu-Sheng Guo; Xiao Chen; Hua Zhang (Applied Geophysics, 2018)

The salinity tolerance of the invasive golden apple snail ( Pomacea canaliculata ) - Song Yang; Jing-ren Zhong; Liu-lan Zhao; Hao Wu; Zong-jun Du; Qiao Liu; Jia-en Zhang; Tai-ming Yan; Xiao-li Huang (Molluscan Research, 2018)

Phytoactinopolyspora halotolerans sp. nov., a halotolerant actinobacterium isolated from a saline soil in Xinjiang, northwest of China - Yang Ji; Wei-Xun Chunyu; En-Yuan Li; Zhang-Gui Ding; Min Yin; Yu-Rong Zhao; Yun Wang; Shu-Kun Tang (Antonie van Leeuwenhoek, 2018)

Genome sequencing brought Gossypium biology research into a new era - Fuguang Li; Zuoren Yang; Zhi Wang; Zhao’en Yang (Science China Life Sciences, 2017)

L1CAM drives oncogenicity in esophageal squamous cell carcinoma by stimulation of ezrin transcription - Jin-Cheng Guo; Yang-Min Xie; Li-Qiang Ran; Hui-Hui Cao; Chun Sun; Jian-Yi Wu; Zhi-Yong Wu; Lian-Di Liao; Wei-Jiang Zhao; Wang-Kai Fang; En-Min Li; Li-Yan Xu; et al. (Journal of Molecular Medicine, 2017)

Hydro-mechanical analysis of rainfall-induced fines migration process within unsaturated soils - Xiao-qin Lei; Zong-ji Yang; Si-ming He; En-long Liu; Henry Wong; Xin-po Li (Journal of Mountain Science, 2017)

Olivibacter flavus sp. nov., a novel endophytic bacterium isolated from the root of Camellia sinensis - Lei Tian; Tong-Wei Guan; Ling-Ling Yang; Kai-Yang Lu; Bing-Bing Liu; Wei-Xun ChunYu; Min Yin; En-Yuan Li; Yang Ji; Xiao-Ping Zhang; Shu-Kun Tang (Archives of Microbiology, 2017)

Anatomy of composition and nature of plate convergence: Insights for alternative thoughts for terminal India-Eurasia collision - WenJiao Xiao; SongJian Ao; Lei Yang; ChunMing Han; Bo Wan; Ji’En Zhang; ZhiYong Zhang; Rui Li; ZhenYu Chen; ShuaiHua Song (Science China Earth Sciences, 2017)

Characterization of a neutral recombinant xylanase from Thermoactinospora rubra YIM 77501T - Yi-Rui Yin; Qing-Wen Hu; Wen-Dong Xian; Feng Zhang; En-Min Zhou; Hong Ming; Min Xiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2017)

Impact of Heat Shock Protein A 12B Overexpression on Spinal Astrocyte Survival Against Oxygen-Glucose-Serum Deprivation/Restoration in Primary Cultured Astrocytes - Xun Xia; Yuan Ma; Li-bin Yang; Jing-ming Cheng; Tao Yang; Ke-xia Fan; Yun-ming Li; En-yu Liu; Lin Cheng; Hai-dong Huang; Jian-wen Gu; Yong-qin Kuang (Journal of Molecular Neuroscience, 2016)

Advances on Bioactive Polysaccharides from Medicinal Plants - Jian-Hua Xie; Ming-Liang Jin; Gordon A. Morris; Xue-Qiang Zha; Han-Qing Chen; Yang Yi; Jing-En Li; Zhi-Jun Wang; Jie Gao; Shao-Ping Nie; Peng Shang; Ming-Yong Xie (Critical Reviews in Food Science and Nutrition, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Sugar-Grafted Cyclodextrin Nanocarrier as a “Trojan Horse” for Potentiating Antibiotic Activity - Min Li; Koon Gee Neoh; Liqun Xu; Liang Yuan; David Tai Leong; En-Tang Kang; Kim Lee Chua; Li Yang Hsu (Pharmaceutical Research, 2016)

Cloning and characterization of the geranylgeranyl diphosphate synthase (GGPS) responsible for carotenoid biosynthesis in Pyropia umbilicalis - Li-En Yang; Xing-Qi Huang; Qin-Qin Lu; Jian-Yi Zhu; Shan Lu (Journal of Applied Phycology, 2016)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

Novosphingobium tardum sp. nov., isolated from sediment of a freshwater lake - Nan Chen; Xue-Jian Yu; Jin-Shui Yang; En-Tao Wang; Bao-Zhen Li; Hong-Li Yuan (Antonie van Leeuwenhoek, 2015)

Sediment prokaryote communities in different sites of eutrophic Lake Taihu and their interactions with environmental factors - Nan Chen; Jin-Shui Yang; Jiang-Hang Qu; Hai-Feng Li; Wei-Jie Liu; Bao-Zhen Li; En Tao Wang; Hong-Li Yuan (World Journal of Microbiology and Biotechnology, 2015)

Cytokine production suppression by culture supernatant of B16F10 cells and amelioration by Ganoderma lucidum polysaccharides in activated lymphocytes - Li-Xin Sun; Wei-Dong Li; Zhi-Bin Lin; Xin-Suo Duan; En-Hong Xing; Miao-Miao Jiang; Ning Yang; Hai-Hua Qi; Yu Sun; Min Li; Yan-Dong Niu; Jie Lu (Cell and Tissue Research, 2015)

Development and evaluation of a new interferon-gamma release assay for the diagnosis of tuberculosis infection in HIV-infected individuals in China - Liang Yu; Pingzheng Mo; Zeping Wei; Ruiling Fu; Mai Yang; Binying Ji; Jian Wang; Shu Li; Amie J. Strong; Neal Touzjian; Nicholas Kushner; Xi-En Gui; et al. (Infectious Diseases, 2015)

Characterization and phylogenetic analysis of α-gliadin gene sequences reveals significant genomic divergence in Triticeae species - GUANG-RONG LI; TAO LANG; EN-NIAN YANG; CHENG LIU; ZU-JUN YANG (Journal of Genetics, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

A fracture enhancement method based on the histogram equalization of eigenstructure-based coherence - Xi-Ying Dou; Li-Guo Han; En-Li Wang; Xue-Hua Dong; Qing Yang; Gao-Han Yan (Applied Geophysics, 2014)

The metabolism of 8-heptadecene in Pyropia (Bangiaceae, Rhodophyta) - Min Zhang; Rui-Xia Li; Chuan-Ming Hu; Li-En Yang; Jun Tang; Qin-Qin Lu; Tao Zhang; Zong-Gen Shen; Song-Dong Shen; Pu Xu; Jian-Yi Zhu (Journal of Applied Phycology, 2014)

Artificial seed production and cultivation of the edible brown alga Sargassum naozhouense Tseng et Lu - En Yi Xie; Dong Chao Liu; Cheng Jia; Xiu Li Chen; Bin Yang (Journal of Applied Phycology, 2013)

Bacterial and archaeal diversities in Y unnan and T ibetan hot springs, C hina - Zhao‐Qi Song; Feng‐Ping Wang; Xiao‐Yang Zhi; Jin‐Quan Chen; En‐Min Zhou; Feng Liang; Xiang Xiao; Shu‐Kun Tang; Hong‐Chen Jiang; Chuanlun L. Zhang; Hailiang Dong; Wen‐Jun Li (Environmental Microbiology, 2013)
Summary Thousands of hot springs are located in the north‐eastern part of the Y unnan– T ibet geothermal zone, which is one of the most active geothermal areas in the world. However, a comprehensive and detailed understanding of microbial diversity in these hot springs is still lacking. In this study, bacterial and archaeal diversities were investigated in 16 hot springs ( pH 3.2–8.6; temperature 47–96° C ) in Y unnan P rovince and T ibet, C hina by using a barcoded 16 S rRNA gene‐pyrosequencing approach. A quificae , P roteobacteria , F irmicutes , D einococcus‐ T hermus and B acteroidetes comprised the large portion of the bacterial communities in acidic hot springs. Non‐acidic hot springs harboured more and variable bacterial phyla than acidic springs. D esulfurococcales and unclassified C renarchaeota were the dominated groups in archaeal populations from most of the non‐acidic hot springs; whereas, the archaeal community structure in acidic hot springs was simpler and characterized by S ulfolobales and T hermoplasmata . The phylogenetic analyses showed that A quificae and C renarchaeota were predominant in the investigated springs and possessed many phylogenetic lineages that have never been detected in other hot springs in the world. Thus findings from this study significantly improve our understanding of microbial diversity in terrestrial hot springs.

Improved methods for basic molecular manipulation of the red alga Porphyra umbilicalis (Rhodophyta: Bangiales) - Li-En Yang; Qiu-Ping Jin; Yu Xiao; Pu Xu; Shan Lu (Journal of Applied Phycology, 2013)

Nkx2-1: a novel tumor biomarker of lung cancer - Li Yang; Min Lin; Wen-jing Ruan; Liang-liang Dong; En-guo Chen; Xiao-hong Wu; Ke-jing Ying (Journal of Zhejiang University-SCIENCE B, 2012)

Thermoactinospora rubra gen. nov., sp. nov., a thermophilic actinomycete isolated from Tengchong, Yunnan province, south–west China - En-Min Zhou; Shu-Kun Tang; Carsten Sjøholm; Zhao-Qi Song; Tian-Tian Yu; Ling-Ling Yang; Hong Ming; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Mechanistic insights into the link between visfatin gene C-1535T polymorphism and coronary artery disease: an in vitro study - Yong-Sheng Wang; Wei Gao; Hong-Fen Li; Ze-Mu Wang; Jun Zhu; Huan Zhao; Jian-Jun Yan; En-Zhi Jia; Zhi-Jian Yang; Lian-Sheng Wang (Molecular and Cellular Biochemistry, 2012)

Diversity of Crenarchaeota in terrestrial hot springs in Tengchong, China - Zhao-Qi Song; Jing-Quan Chen; Hong-Chen Jiang; En-Min Zhou; Shu-Kun Tang; Xiao-Yang Zhi; Li-Xin Zhang; Chuan-Lun L. Zhang; Wen-Jun Li (Extremophiles, 2010)

Improvement of heart function in postinfarct heart failure swine models after hepatocyte growth factor gene transfer: comparison of low-, medium- and high-dose groups - Zhi-jian Yang; Bo Chen; Zhang Sheng; Ding-guo Zhang; En-zhi Jia; Wei Wang; Dong-chao Ma; Tie-bing Zhu; Lian-sheng Wang; Chun-jian Li; Hui Wang; Ke-jiang Cao; et al. (Molecular Biology Reports, 2010)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Association of the mutation for the human carboxypeptidase E gene exon 4 with the severity of coronary artery atherosclerosis - En-Zhi Jia; Jie Wang; Zhi-Jian Yang; Tie-Bing Zhu; Lian-Sheng Wang; Hui Wang; Chun-Jian Li; BO Chen; Ke-Jiang Cao; Jun Huang; Wen-Zhu Ma (Molecular Biology Reports, 2009)

Differential generation of hydrogen peroxide upon exposure to zinc and cadmium in the hyperaccumulating plant specie (Sedum alfredii Hance) - Yue-En Chao; Min Zhang; Sheng-ke Tian; Ling-li Lu; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2008)